The Relationship Between Risk Factors And Stunting Incidence In Children Aged 24-59 Months In The Working Area Of Semen Community Health Center, Kediri Regency, 2023 - Rahma Kusuma Dewi; Dhita Kris Prasetyanti; Meirna Eka Fitriasnani; Lindha Sri Kusumawati; Raras Sucma Ambar; Siti Khotimah (Journal for Quality in Women's Health, 2025)
Stunting, caused by malnutrition during pregnancy and early childhood, leads to growth failure and cognitive delays. Key risk factors include maternal nutrition, breastfeeding practices, low birth weight (LBW), birth length, and neonatal health. This study analyzes the relationship between these factors and stunting in children aged 24-59 months in Puskesmas Semen, Kediri Regency, in 2023. Using a correlational design, data were collected in August 2023 through simple random sampling. Chi-square tests and logistic regression were used for analysis. The findings indicate that breastfeeding history, LBW, and birth length significantly impact stunting, with LBW as the strongest risk factor (RR = 2.19). Prevention efforts should focus on exclusive breastfeeding, reducing LBW, and improving maternal nutrition. Sustainable stunting interventions require collaboration among healthcare professionals, the government, and communities..